Evaluation of the Efficacy of Nasal Sedation Midazolam Compared with Dexmedetomidine in the Management of Uncooperative Children with Down Syndrome during Dental Treatment - Mohamad Nabil Hamod; Chaza Kouchaji; Faten Rostom; Hasan Alzoubi; Imad Katbeh; Nikolay Tuturov (International Journal of Dentistry)
Objective. This study aimed to compare the intranasal administration of midazolam and dexmedetomidine in uncooperative children with Down syndrome. Materials and Methods. The sample consisted of 20 children with Down syndrome aged 5 to 11 years who were divided equally into two groups: Group 1 (experimental) nasal dexmedetomidine and Group 2 (control) nasal midazolam. The efficacy of both the drugs was evaluated according to Ohio State University Behavioral Rating Scale (OSUBRS), University of Michigan scale (UMSS), and Houpt general behavior scale. Results. Both substances have been effective in the management of children with Down syndrome. There were no statistically significant differences for Ohio State University Behavioral Rating Scale (OSUBRS) (P value = 0.631), University of Michigan scale (UMSS) (P value = 0.739), and Houpt general behavior scale (P value = 0.481). Conclusion. Both midazolam and dexmedetomidine nasal can be used to sedate children with Down syndrome.